Integrating interactive response systems and deliberate practice in a level design for games course: effects on intrinsic motivation, design anxiety, self-efficacy, and learning achievement - Kai-Ming Yang (Cogent Education, 2025)
This study aimed to improve student learning outcomes by integrating an interactive response system (IRS) and deliberate practice (DP) into a Level Design for Games course. Previously, this theory-and-practice course was lecture-oriented, emphasized game level design and its application, and offered classic games to demonstrate level design concepts. However, it lacked mutual interaction between the teacher and the students and decreased students’ intrinsic motivation and self-efficacy when they did not have enough design experience. To address these issues, this study integrated an IRS (ZUVIO) and DP into the course to improve the curriculum design. A single-group pretest-posttest experimental design was employed, with 45 participants completing valid pretest and posttest questionnaires. The course was divided into theoretical and practical parts. In the theoretical part, ZUVIO was employed as an intervention. In the practical part, five steps of DP designed by this study were adopted: understanding, imitating, analyzing, feedback, and deriving. The statistical results confirm that the instructional approach effectively maintained participants’ high intrinsic motivation and low design anxiety while significantly improving their self-efficacy and learning achievement. These benefits were observed in students with diverse game level design capabilities. It is suggested that teachers adopt IRS and DP in their teaching to make lectures more engaging and increase students’ practical capabilities and self-efficacy.